2015
DOI: 10.5194/tc-9-837-2015
|View full text |Cite
|
Sign up to set email alerts
|

A process-based approach to estimate point snow instability

Abstract: Abstract. Snow instability data provide information about the mechanical state of the snow cover and are essential for forecasting snow avalanches. So far, direct observations of instability (recent avalanches, shooting cracks or whumpf sounds) are complemented with field tests such as the rutschblock test, since no measurement method for instability exists. We propose a new approach based on snow mechanical properties derived from the snow micropenetrometer that takes into account the two essential processes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 45 publications
(55 reference statements)
4
63
0
Order By: Relevance
“…However, at the slope scale, 3-D effects, slope-transverse propagation, terrain, and snowpack variability (Schweizer et al, 2008;Gaume et al, 2015a) might make the process even more complex. Nevertheless, it was shown that the critical crack length correlates very well with signs of instability (Reuter et al, 2015). In particular, they showed that no signs of instability were recorded for a c > 0.4 m while whumpfs, cracks, and avalanches were observed for a c < 0.4 m. Hence, our new model of critical crack length can be of major importance in view of avalanche forecasting.…”
Section: Relevance and Limitationsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, at the slope scale, 3-D effects, slope-transverse propagation, terrain, and snowpack variability (Schweizer et al, 2008;Gaume et al, 2015a) might make the process even more complex. Nevertheless, it was shown that the critical crack length correlates very well with signs of instability (Reuter et al, 2015). In particular, they showed that no signs of instability were recorded for a c > 0.4 m while whumpfs, cracks, and avalanches were observed for a c < 0.4 m. Hence, our new model of critical crack length can be of major importance in view of avalanche forecasting.…”
Section: Relevance and Limitationsmentioning
confidence: 96%
“…In this paper, the multilayered character of the slab was not accounted for, for clarity reasons since the phenomenon is already very complex. However, the elastic moduli of the slab layers have a very important influence on slab deformation and thus on the critical crack length (Reuter et al, 2015). For the comparison with the experiments, the elastic modulus was computed from the average slab density.…”
Section: Relevance and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations